Environmental Health Evaluation of the Tanjung Bias Beach Tourism Area, Batu Layar District, West Lombok Regency - Ario Sukma; R Raihan Amiruzzuhdi; Lalu Muhammad Aby Dujana; Rachmawati Noviana Rahayu (Tinta Emas Publisher, 2025)
Tanjung Bias Beach is a coastal tourism destination in West Lombok Regency that supports local economic activities through visitor arrivals, food vendors, and community-based services. However, increased tourism activity may create environmental health risks when sanitation facilities, clean water provision, waste management, food hygiene, and environmental education are not adequately managed. This study aimed to evaluate the environmental health condition of the Tanjung Bias Beach tourism area in Batu Layar District, West Lombok Regency. A descriptive qualitative approach with normative evaluation was applied. Data were collected through field observations, environmental health inspection checklists, brief interviews with managers and business actors, documentation, and literature review. The findings were assessed against Indonesian regulatory standards, particularly Ministry of Health Regulation No. 2 of 2023, Government Regulation No. 66 of 2014, Law No. 18 of 2008, and Law No. 32 of 2009. The results show that clean water for non-consumption purposes is available through storage tanks and generally functions well; however, the water is not suitable for drinking because of brackish characteristics that may indicate seawater intrusion. Sanitation facilities, handwashing stations, traders’ personal protective equipment, environmental education, and routine beach-cleaning programs remain inadequate. Therefore, Tanjung Bias Beach requires strengthened sanitation infrastructure, improved waste management, food hygiene guidance, environmental education, and cross-sector collaboration to support a healthy, safe, and sustainable coastal tourism area.